(untitled) (Journal of Human Sciences, 2024)
The study of inscriptions, rock drawings, Pharaonic sources, and classical writings has provided us with a clear idea about ancient Libyan clothing. Libyans made their clothes from leather and wool, and traditional Libyan attire consisted of clothing that cover and protect private parts which was the oldest attire known to Libyans and was worn by adult Libyans. One of the Libyan clothes is "Abaya" (cloak), as described in the Akakus paintings, representing human figures wearing cloaks. The abaya is considered one of the most famous clothes worn by Libyans during the modern state in the Pharaonic era. Strabo also mentioned Libyans wearing wide abayas without belts. Libyans have been interested in hairstyling since ancient eras and the rocky mountains of the Akakus are filled with scenes that represent different hair styling techniques for both men and women. The Pharaonic inscriptions also indicate that the Libyans had various ways of styling their hair. Classical authors also referred to the strands and Libyans’ hair while discussing on Libyan tribes. Libyans made their simple shoes of natural leather (goat and cow) and the inscriptions and rock drawings in the Acacus confirm that Libyans wore shoes. The Egyptian inscriptions also mentioned the shoes and sandals worn by Libyans. Libyans were interested in their adornment and crafted their jewelry from raw materials available in their environment such as feathers, anklets, bracelets, and necklaces. The Acacus rock art represented the jewelry worn by Libyans. Libyans have appeared in Pharaonic artifacts adorned with necklaces bracelets and other ornaments. Herodotus mentioned adornment adorned by Libyan women, the Libyans knew tattoo and used it on their arms and legs. The Pharaonic inscriptions revealed various kinds of tattoos on the bodies of the Libyans.